Ultrasound combined with pH-shifting improved the emulsification and stability of coconut meal protein isolate by modifying physicochemical properties and intermolecular forces - Jin Guo; Jiale He; Wenlin Xu; Zewei Ma; Rongli Li; Wenjie Xia; Xinpeng Bai; Zhaoxian Huang; Yan Tian; Hongjian Zhang (Ultrasonics Sonochemistry, 2025)
This study investigated the effects of ultrasound combined with acidic/alkaline pH-shifting (U-C/U-K) and acidic/alkaline pH-shifting combined with ultrasound (C-U/K-U) on the physicochemical properties and emulsification performance of Coconut Meal Protein Isolate (CMPI). The results demonstrated that these modification treatments reduced the particle size and polydispersity index of CMPI, increased its net charge, and improved its solubility, except in the group subjected to the ultrasound followed by acid pH-shifting (U-C). These modifications also promoted the conversion of disulfide bonds into free sulfhydryl groups. Among the various molecular interactions, hydrogen bonding and hydrophobic interactions played a more significant role in the formation of CMPI particles than electrostatic interactions and disulfide bonds. Furthermore, the U-C and C-U (acid pH-shifting followed by ultrasound) treatments reduced the particle size and interfacial tension of CMPI-based emulsions while enhancing their emulsification activity index and emulsification stability index. Compared to the Control Group (CON), CMPI-based emulsions treated with C-U exhibited improved emulsifying stability under thermal stress, varying pH conditions, and in the presence of NaCl. Overall, the acidic pH-shifting combined with ultrasound sequential treatment (C-U) proved more effective in enhancing the emulsification properties of CMPI.